Giant cell arteritis associated with chronic active Epstein-Barr virus infection - A. Giardina; A. Rizzo; A. Ferrante; G. Capra; G. Triolo; F. Ciccia (PAGEPress Publications, 2013)
Giant cell arteritis is an inflammatory vasculopathy that preferentially affects medium-sized and large arteries. A viral cause has been suspected but not confirmed in polymyalgia rheumatica and giant-cell arteritis. We report the case of a 81-year-old female who suffered from chronic active Epstein-Barr virus infection and developed giant cell temporal arteritis.